Housing policy and price effects on housing wealth distribution in Singapore. - Chan, Joy Yuen Yee. (2013)
Homeownership and other factors... have brought about an increase in housing prices. The change in prices could have result the housing wealth distribution in Singapore to change too. Social problems like inequality might have resulted.